Factors Affecting the Development of Secondary Schools Libraries Basra City - Kanaan Saeed , Researcher. Moayad; Abdel-Rahman Abdel-Wahwd , Prof. Dr. Amal (Basra studies journal, 2023)
The research aims at identifying the factors affecting the development of secondary schools libraries in terms of (location and building, laws and legislation, school administration, librarians, library group, and information services). Using the tools represented in the interview and observation, the researcher reached several results 1- Poor work in the legislative aspect and the law of school libraries. 2-The financial aspect: no ambitious financial disciplines available for the development of school libraries. 3- Lack of interest in the proposals and communications issued by the Libraries Department in the Ministry regarding taking into account the location and building of the library for the construction of new schools.